Heuristic Based Placement Technique for Distributed Generation - Omar, Aliman (2011)
In this paper, a heuristic DG optimization technique for radial distribution feeders is proposed. Significant search space reductions obtained through a small number of DG tests is offered. A sufficient sensitivity test analysis applicable for DG applications is proposed. Sample test system is examined using the proposed technique and the results are compared with those obtained via other method. The suggested technique succeeds in solving different test cases. A comparative study validates the practical concerns of the proposed method.